2013
DOI: 10.1590/0004-282x20130061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early spasticity treatment on children with hemiplegic cerebral palsy: a preliminary study

Abstract: Objective: To compare motor and functional performance of two groups of children with hemiplegic cerebral palsy (HCP). Only the study group (SG) received early treatment of spasticity with botulinum neurotoxin type A (BXT-A). Methods: Gross Motor Function Measure (GMFM), functional performance (Pediatric Evaluation of Disability Inventory -PEDI), range of movement, gait pattern (Physician Rating Scale -PRS) and the speed of hand movements were considered. Results: The SG, composed of 11 HCP (45.64±6.3 months),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Although it is imperative to start the CP treatment at the earliest possible time, great attention must also be put on a specific treatment process in relation to particular age. Delay in initiating treatment and lack of systematic method in accordance with age may result in secondary problems, such as joint contracture, muscle shortening, and deformity, which in turn reduce treatment efficacy and impede functional improvement that could otherwise be enhanced with a proper treatment strategy [ 10 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is imperative to start the CP treatment at the earliest possible time, great attention must also be put on a specific treatment process in relation to particular age. Delay in initiating treatment and lack of systematic method in accordance with age may result in secondary problems, such as joint contracture, muscle shortening, and deformity, which in turn reduce treatment efficacy and impede functional improvement that could otherwise be enhanced with a proper treatment strategy [ 10 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that physical/motor aspects such as flexibility, coordination, and balance in young individuals with CP benefit from dance practice and are important to prevent inactivity leading to loss of strength, endurance, and mobility in these individuals 11,12 . While dancers seek to optimize their performances, the vast repertoire of styles and body techniques that comprise hip-hop 24 serve as a motivation, which is recognized as key to neuroplasticity 25 while stimulating motor learning 26 .…”
Section: Discussionmentioning
confidence: 99%
“…This demands from the dancer body awareness and trunk mobility 24 , preventing complications and deterioration of his or her health status 27 . Rhythmic alternation suggests that movements are executed repetitively, which benefits motor learning and reduces spasticity 26 . The movements of the trunk and lower and upper limbs can be trained separately to be executed simultaneously and continuously, in a coordinated way and synchronized with the rhythm 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies clearly support preventive strategies to avoid, delay or reduce the emergence of several pathological conditions associated with neurological diseases, such as chronic pain or spasticity [35]. Similarly, after acute supra-sacral SCI, early pudendal nerve stimulation (PNS) and sacral neuromodulation (SNM) have been reported to successfully obviate DO, enhancing the potential of preventive measures against SCI-related DO [6,7].…”
Section: Introductionmentioning
confidence: 99%